Global Hop Domination Numbers of Graphs (European Journal of Pure and Applied Mathematics, 2021)
A set S ⊆ V (G) is a hop dominating set of G if for each v ∈ V (G) \ S, there exists w ∈ S such that dG(v, w) = 2. It is a global hop dominating set of G if it is a hop dominatingset of both G and the complement of G. The minimum cardinality of a global hop dominatingset of G, denoted by γgh(G), is called the global hop domination number of G. In this paper, we study the concept of global hop domination in graphs resulting from some binary operations.